Carbon‐Selective Difluoromethylation of Soft Carbon Nucleophiles with Difluoromethylated Sulfonium Ylide. Issue 11 (25th September 2018) - Zhu, Jiansheng; Zheng, Hanliang; Xue, Xiao‐Song; Xiao, Yisa; Liu, Yafei; Shen, Qilong
Abstract: A highly carbon‐selective difluoromethylation of soft carbon nucleophiles including β‐ketoesters, malonates, oxindoles, benzofuranones and ketene silyl acetals with a difluoromethylated sulfonium ylide under mild conditions was described. Mechanistic studies suggest that these difluoromethylating reactions proceed via a difluorocarbene pathway. Abstract : A highly carbon‐selective difluoromethylation of soft carbon nucleophiles including β‐ketoesters, malonates, oxindoles, benzofuranones and ketene silyl acetals with a difluoromethylated sulfonium ylide under mild conditions was described. Mechanistic studies suggest that these difluoromethylating reactions proceed via a difluorocarbene pathway.